Communication and Technology: Ida Orlando's Theory Applied. (October 2018) - Gaudet, Cynthia; Howett, Maeve
Today's bedside nurse communicates with patients in an environment that incorporates a wide variety of technology, from simple instruments such as a penlight to complex devices including cellphones, interactive computers, and computerized intravenous pumps. This is an excellent time to examine communication between the nurse and patient in today's fast-paced, technologically driven environment. Orlando's theory of the dynamic nurse-patient relationship provides a theoretical framework for understanding that communication. The proposed model affords a visual demonstration to assist in teaching communication.